Microstructure and Mechanical Properties of Nb–Ti–V–Zr Refractory Medium-Entropy Alloys - Jia, Yuefei; Zhang, Liangbo; Li, Peiyou; Ma, Xindi; Xu, Long; Wu, Shiwei; Jia, Yandong; Wang, Gang (Frontiers in Materials, 2020)
The low-density refractory medium entropy alloys (NbTiVZr, Nb0.5TiVZr and NbTiV) were produced by vacuum arc melting and then heat-treated at 1200 ℃ for 1 h, following by water quenching and finally annealed at 500 ℃ for 0.5 h. The microstructures, elevated temperature mechanical properties and thermal expansion behavior were investigated correspondingly. All the alloys are characterized by BCC structure with grain size around 85 ~ 135 m. Results demonstrated that NbTiVZr alloy exhibits relative high yield strength and specific strength at elevated temperature. Moreover, low coefficient of thermal expansion was also obtained for this alloy when the temperature is below 750 °C. This study provided a guidance for the engineering application of low-density refractory medium entropy alloys at elevated temperature.